PENGARUH DOSIS PUPUK BOKASI PADAT DAN KONSENTRASI PUPUK ORGANIK CAIR (POC) BIOMASSA DAUN GAMAL TERHADAP PERTUMBUHAN DAN HASIL TANAMAN CABAI RAWIT (Capsicum frutescens L.) - Yosefina Rofina Yuliaty Gandut; Eurosia F Supa; Elias St O Nguru (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
The research was conducted in the East Penfui village, Kupang district. Taking place from June to October 2022. The aim is to determine the effect of doses of solid bokashi fertilizer and concentration of liquid organic fertilizer of gamal leaf biomass on the growth and yield of cayenne pepper plants and to find out the combination of doses of solid bokashi fertilizer and concentration of liquid organic fertilizer of gamal leaf biomass which provides growth and the best chili plants. This study used Non Factorial RAK with 13 treatment combinations and 6 replications. Treatments tried: Gamal leaf bokashi (D) at a dose of 5 tons/ha, 15 tons/ha and without gamal leaf bokashi fertilizer and liquid organic fertilizer (M) with POC concentrations of 40%, 80% and 120%. The variables studied were plant height, secondary branches, productive branches, fresh fruit and total fruit weight. The results showed that there were differences in the combination of doses of solid bokashi fertilizer and concentration of liquid organic fertilizer of gamal leaf biomass which had a significant effect on the growth and yield of cayenne pepper plants. The combination treatment of solid bokashi fertilizer doses of 15 tons/ha and POC concentration of gamal leaf biomass of 120% gave significantly better cayenne pepper plant growth resulting in yields in the form of a total harvested fruit of 24.17 fruits/plant and a total harvested fresh fruit weight of 24.83 grams/plant.